Revisiting Women’s Empowerment in the Dotuman Angon Livestock Group: A Theoretical Analysis Based on Naila Kabeer’s Framework - Ahmad Kharis; Suryo Ediyono (KOMUNITAS, 2025)
Women’s empowerment in the Dotuman Angon livestock group through the theoretical framework of Naila Kabeer. The study is grounded in the understanding that empowerment is not solely an economic process but a transformation of power relations shaped by social and cultural structures. Using a descriptive qualitative approach based on a literature review and contextual analysis, this study explores how access to resources, decision-making capacity, and meaningful achievements are experienced by women within the livestock group. The findings indicate that while development programs may increase productivity and household assets, these outcomes do not necessarily translate into genuine empowerment for women when agency and control over decisions remain limited. The study highlights the importance of applying a multidimensional and gender sensitive approach in community empowerment programs to ensure that women are not merely beneficiaries of development initiatives, but active agents in shaping their own lives.